Corrie Ten Boom : keeper of the angels' den - Benge, Janet, 1958-; Benge, Geoff, 1954- (Seattle, WA : YWAM Pub., 1999)
Relates events in the life of the Dutch woman who survived imprisonment in Nazi concentration camps to become a Christian missionary.
Includes bibliographical references (p. 201).
Keywords: Ten Boom, Corrie -- Juvenile literature; Christian biography -- Netherlands -- Juvenile literature; Ten Boom, Corrie; Missionaries; Women -- Biography